A randomized controlled trial to evaluate the impact of pharmacist-led clinical interventions on the health-related quality of life among TB patients - Khan, Farman Ullah; Khan, Faiz Ullah; Aqeel, Muhammad Tahir; Hayat, Khezar; Chang, Jie; Rehman, Asim ur; Fang, Yu (Frontiers in Pharmacology, 2023)
Background: The study was designed to evaluate the impact of pharmacist-led clinical interventions on the health-related quality of life among tuberculosis patients in Pakistan. Methods: A randomized, controlled prospective study was carried out in a Pakistan Institute of Medical Sciences hospital tuberculosis (TB) control center. Participants who visited the TB center between September 2020 and December 2021 were randomly assigned to two clusters, the usual care group (UC group) vs. the intervention group (pharmaceutical care group), in a 1:1 ratio by a simple envelope technique. In the intervention group, a patient received centered care that encompassed informed decision-making, which can increase the quality of care and monitoring of adverse drug events. However, the control group received routine TB treatment at the hospital. The EuroQol-5D-3L instrument was used to assess the health-related quality of life (HRQoL) at the baseline and in the third and sixth months of the treatment time period. Results: A total of 503 patients were eligible, of which only 426 patients were included in this study. At the end of the study, n = 205 of the patients in the intervention group and n = 185 of those in the control group were analyzed. In the intervention group, the EQ-5D-3L health utility score improved significantly (p < 0.001) (from the baseline mean ± SD, 0.40 ± 0.36, to 6 months of treatment, 0.89 ± 0.09, while in the control group from 0.42 ± 0.35 to 0.78 ± 0.27). In multivariate regression analysis, the variables that remained statistically associated (p < 0.001) with the HRQoL (unstandardized β [95% confidence interval]) of the control group were as follows: gender, female vs. male (-0.039 [-0.076 to -0.003]); body weight, less than 40 kg vs. more than 40 kg (-0.109 [-0.195 to -0.024]); patients with any comorbidity vs. without comorbidity (-0.136 [-0.252 to -0.020]); and smokers vs. non-smokers (-0.204 [-0.291 to -0.118]). The study did not find any statistically significant associations between the intervention group’s variables and the HRQoL. Conclusion: Patient-centered care interventions led by pharmacists as part of care coordination enhanced the HRQoL for TB patients significantly. According to this study, clinical pharmacists should be included in the interdisciplinary clinical staff for TB patient management.